The effects of different methods of Ankle Foot Orthosis fabrication on plantar pressure in asymptomatic adults - V. moradi; M. kamyab; M. arvin; Gh. aminian (Afarand Scholarly Publishing Institute, 2011)
Background: Ankle foot orthoses are effective in controlling wide-range orthopedic deformities. Two difference methods (prefabricated and custom-made) were used for construction of AFOs. However, the high cost of custom devices prevents some patients from purchasing them. Some patients and orthotics prefer to prefabricated devices. The purpose of this study was to examine whether the prefabricated AFOs (PAFO) can provide similar pressure distribution as custom-made AFO (MAFO) in healthy people. Objective: The purpose of the current study was to the comparison of two different fabrication methods of AFO by plantar pressure in asymptomatic adults. Methods: In this study, peak pressures (PP) were recorded with Pedar-x system while pressure insole was placed between foot and AFO. Twenty-four subjects participated in this study completed a total of three 8-m walking trials in each of two types of AFOs. Results: The PP was significantly decreased in the heel (P < 0.004), first metatarsal (P < 0.001), and second metatarsal head regions (P < 0.003) in MAFO when compared to PAFO but PP was significantly decreased in second toe (P < 0.027) and toes 3-5( P < 0.003) regions in PAFO in comparison with MAFO. No significant differences were observed at the other regions. Conclusion: The results of this study demonstrated that significant differences were observed in PP at the almost regions when comparing two AFOs. So they should carefully prescribe for using with various disorders.